Another Iron Age Grave on the Isthmus near Ston (Archaeologia Adriatica, 2009)
The grave was discovered by chance in the late 1960s when foundations of a house were dug some 200 m east of city gate. Finds were collected by an unknown finder who gave it to the former Institute for the Protection of the Monuments in Dubrovnik. Only several sherds of ceramic ware were found, an omega pin and a stone bead. Nevertheless, it is important to publish these modest finds having in mind lack of research at prehistoric sites in Ston. The ware is of Greek origin: Corinthian skyphoi or their Attic variants which can probably be dated to the 4th century BC. On the basis of this and other chance finds in the immediate vicinity, particularly on Prevlaka, it is reasonable to assume the existence of a flat necropolis which can be broadly dated to the period from the 5th to late 4th century BC
Keywords: Ston isthmus; flat necropolis; Greek pottery; skyphos; omega pin